(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze which website quality factors to induce consumer’s repurchase intention in the tourism sector utilizing Online Travel Agent as a platform, with the mediation of perceived value. The authors used a quantitative approach with a minimum of 302 samples. The questionnaires were distributed to a broad audience in Indonesia written in Bahasa Indonesia. The authors then analysed the questionnaire data using path analysis. The findings suggest that (1) all of the website quality factors that were tested, based on the data results 5 out of 7 had direct positive relation to influence to perceived value (2) second regression which were to assess perceived value, also has direct positive relation to repurchase intention. This study demonstrates insight on which website quality components give direct implications on consumer’s repurchase intention in the mediation of perceived value for Indonesia market. Research result show that customers’ intentions in Indonesia come back to use websites travel Agent that affects perceived value were based on 5 variables: security, price, brand image, ease of use, and quality information (popular destinations). Furthermore, the hypothesis test also shows a positive result regarding the influence of perceived value on repurchase intention.